BASEL-VANAGAITE-SMIRIN-YOSEF SYNDROME - Mursalova, Z.Sh.; Rakhimova, N.C.; Nasirova, S.R.; Abbasaliyeva, A.I.; Alkhazova, A.F. (World of Medicine and Biology, 2024)
Basel-Vanagaite-Smirin-Yosef Syndrome is a rare syndrome of genetic mental retardation caused by an autosomal recessive mutation of the MED 25 gene. 112 case histories of patients aged 1 month-3 years old with seizures were analyzed. During observation symptoms, characteristic for Basel-Vanagaite-Smirin-Yosef syndrome were detected. By comparing the frequency of clinical symptoms in this patient with others, we found that this syndrome is more characterized by a combination of sparse eyebrows and hair, wide forehead, retrognathia, hypertelorism with malformations of the brain and heart, and for early diagnosis an approach based on deep research should be recommended. A multidisciplinary approach to symptom management and timely initiation of prophylaxis of complications can improve the quality of life of these patients.